Factors influencing knowledge of synthetic cannabinoids: Study conducted among future healthcare professionals - Skoko Nina M.; Sazdanić Darija B.; Samojlik Isidora N.; Kolarš Bela Š.; Miljković Ana R.; Mijatović-Jovin Vesna M. (Srpsko lekarsko drustvo, 2022)
Introduction: Although the consumption of synthetic cannabinoids (SC) has become more and more widespread recently, future healthcare professionals, according to the currently available curriculum, receive minimal information about diagnosis and treatment thereof. Aim: The main goal is to assess the level of knowledge of students of health professions about SC and examine the factors that influence that knowledge. Material and methods: A cross-section academic study was conducted among 510 students of medicine, dentistry and pharmacy at the Faculty of Medicine, University of Novi Sad, Serbia, during 2017 using a structured questionnaire. Results: Forty-nine percent of students answered positively to the question if they knew what SCs were, whereas when they were offered three definitions regarding SCs-92.2% gave the correct answer, with male students demonstrating a better knowledge than female ones (p=0.014). There was no correlation between previous knowledge about SCs and professional qualifications of the student's parents (p=0.953 mother, p=0.500 father) or the student's social media profile existence (p=0.057). Pharmacy students showed better previous knowledge about SCs in comparison with students of other courses (p=0.000) as well as the final year students when compared to those from the 1 st and 2 nd year of study (p=0.000). The repetition of a year level did not affect student's knowledge (p=0.616). Students with experience in alcohol usage showed better previous knowledge of SCs in comparison with alcohol non-users (p=0.008). However, most of the respondents answered "do not know" on the majority of statements about SCs offered. Conclusion: Superficiality in students' knowledge and insufficiency of formal education contributes to the necessity for revising curriculum regarding SCs for future health care professionals.